The effects of the inhaled formaldehyde during the early postnatal period in the hippocampus of rats: A morphological and immunohistochemical study - Songur, A; Akpolat, N; Kus, I; Ozen, OA; Zararsiz, I; Sarsilmaz, M (John Wiley & Sons Ltd, 2003)
The aim of this study was to investigate the effects of formaldehyde (FA) gas inhalation during the early postnatal period on the heat shock proteins 70 kDa (Hsp70) synthesis and morphological changes in the hippocampus in developmental process of rats and to determine whether the changes was reversible or not. Neonatal rats were exposed to 0 (control), 6 and 12 ppm FA gas throughout 30 day period following the birth. After the exposure to FA, some animals from each concentration group were decapitated at the day 30. Despite cessation of FA exposure, other groups were left for decapitation until the days of 60(th) and 90(th). The brain samples were stained with Hsp70 as immunohistochemically and H&E. In the samples, pyramidal cell layer in the hippocampus was examined. Hsp70 (+) neurons were found in the hippocampus of rats that inhaled FA on the 30(th) day. Furthermore, a considerable increase on the count of pyknotic neurons in these groups. But, on the other hand, in the 60(th) and 90(th) days, Hsp70 immunostaining and the count of pyknotic cells were found to be diminishing in FA inhaled groups. In conclusion, inhalation of FA gas in cytotoxic concentrations during early postnatal period causes increase in Hsp70 synthesis and damages the rat's hippocampus. Diminishment or disappearance of these negative changes in the 60(th) and 90(th) days indicates a reversible change in rats.
6th National Congress of Anatomy -- SEP 03-07, 2001 -- EDIRNE, TURKEY
Keywords: inhaled formaldehyde; hippocampus; Hsp70; postnatal development